Representation and Processing of Lexical Tone and Tonal Variants: Evidence from the Mismatch Negativity - Li, Xiaoqing; Chen, Yiya (PloS one, 2015)
Pronunciation variation is ubiquitous in the speech signal. Different models of lexical representation have been put forward to deal with speech variability, which differ in the level as well as the nature of mental representation. We present the first mismatch negativity (MMN) study investigating the effect of allophonic variation on the mental representation and neural processing of lexical tones. Native speakers of Standard Chinese (SC) participated in an oddball electroencephalography (EEG) experiment. All stimuli have the same segments (ma) but different lexical tones: level [T1], rising [T2], and dipping [T3]. In connected speech with a T3T3 sequence, the first T3 may undergo allophonic change and is produced with a rising pitch contour (T3V), similar to the lexical T2 pitch contour. Four oddball conditions were constructed (T1/T3, T3/T1, T2/T3, T3/T2; standard/deviant). All four conditions elicited MMN effects, with the T1-T3 pair eliciting comparable MMNs, but the T2-T3 pair asymmetrical MMN effects. There were significantly greater and earlier MMN effects in the T2/T3 condition than that in the reversed T3/T2 condition. Furthermore, the T3/T2 condition showed more rightward MMN effects than the T2/T3 condition and the T1-T3 pair. Such asymmetries suggest co-activation of long-term memory representations of both T3 and T3V when T3 serves as the standard. The acoustic similarity between the activated T3V (by the standard T3) and the incoming deviant stimulus T2 induces acoustic processing of the tonal contrast in the T3/T2 condition, similar to that of within-category lexical tone processing, which is in contrast to the processing of between-category lexical tones observed in the T2/T3, T1/T3, and T3/T1 conditions.